Copper deficiency affects the developmental competence of porcine oocytes matured in vitro - Choi, Hyerin; Oh, Dongjin; Kim, Mirae; Cai, Lian; Lee, Joohyeong; Kim, Eunhye; Lee, Gabsang; Hyun, Sang-Hwan (Frontiers in Cell and Developmental Biology, 2022)
The trace element Cu is required for the activity of various enzymes essential for physiological processes. In this study, we elucidated the copper transport system in porcine follicular cells and investigated the effect of Cu chelation during the in vitro maturation (IVM) of porcine oocytes and subsequent embryonic development after parthenogenetic activation (PA). Cu chelation was induced by adding tetraethylenepentamine (TEPA) to the maturation media (TCM199-PVA). First, we identified the localization and relative levels of the copper transporter CTR1 in follicular cells. The level of CTR1 protein was the highest in mature cumulus cells; moreover, CTR1 was mainly localized in the cytoplasmic vesicular compartment in oocytes, whereas it was evenly distributed in the cytoplasm in cumulus cells. A total of 42 h after IVM, the TEPA-treated group showed reduced maturation rates compared to those of the control (p < 0.05). This negative effect of TEPA disappeared when it was added to the media with Cu (Cu + TEPA group). The TEPA treatment during IVM significantly increased the mRNA levels of the Has2 gene, which is related to cumulus expansion (p < 0.05). Both Cu supplementation and chelation significantly increased the reactive oxygen species (ROS) levels in porcine oocytes (p < 0.05). When we analyzed the transcript levels of folliculogenesis-related genes in Cu chelation conditions, only the expression of MAPK3 in cumulus cells significantly increased compared to that of the control. We also evaluated the subsequent embryonic development of PA embryos. TEPA-treated oocytes showed significantly decreased blastocyst formation rates compared to those of the control. The TEPA-induced toxic effect was alleviated when Cu was added with TEPA. Our findings suggest that the Cu transport system plays an important role in the porcine follicular development process and that the Cu deficiency negatively affects porcine oocyte maturation, as well as their subsequent developmental competence.